Artificial Intelligence and the New Wave of Information Technology (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The article delves into the transformative impact of Artificial Intelligence (AI) on Information Technology (IT), highlighting the emergence of a new wave of technological innovation. It explores the role of AI in driving automation, enhancing data analytics, improving user experiences, bolstering cybersecurity, and accelerating research and development. The discussion extends to the ethical and societal implications of AI integration in IT, addressing concerns like privacy, bias, and regulation. The article also anticipates future trends, pointing to the increasing ubiquity of AI and its potential convergence with technologies like quantum computing and IoT, signaling a redefinition of IT landscapes and opening new avenues for innovation and efficiency.